2024
DOI: 10.1002/zamm.202300302
|View full text |Cite
|
Sign up to set email alerts
|

Integrated intelligence of inverse multiquadric radial base neuro‐evolution for radiative MHD Prandtl–Eyring fluid flow model with convective heating

Zeeshan Ikram Butt,
Iftikhar Ahmad,
Muhammad Shoaib
et al.

Abstract: In this communication, a new stochastic numerical paradigm is introduced for thorough scrutinization of the magnetohydrodynamic (MHD) boundary layer flow of Prandtl–Eyring fluidic model along a stretched sheet impact on thermal radiation as well as convective heating scenarios by exploiting the accurate approximation knacks of ANNs (artificial‐neural‐networks) modeling by using the inverse multiquadric (IMQ) function optimized/trained with well‐reputed global search with genetic algorithms (GAs) and local sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Some key investigations related to the fluidic system performance are described in the refs. [11][12][13]. The authors found very interesting heat transfer results for various sorts of nanofluids and suggested these as better for numerous engineering applications.…”
Section: Introductionmentioning
confidence: 96%
“…Some key investigations related to the fluidic system performance are described in the refs. [11][12][13]. The authors found very interesting heat transfer results for various sorts of nanofluids and suggested these as better for numerous engineering applications.…”
Section: Introductionmentioning
confidence: 96%